Eco-Friendly Alternatives to Natural Aggregates in Road Construction: A Case Study Using Slag and Moorum - Sharma, Manish; Singh, Akhand Pratap; Birali, R. R. L. (International Journal of Research in Interdisciplinary Studies, 2025)
The increasing scarcity of natural aggregates has become a pressing issue in the road construction industry, primarily due to the high demand for materials and the energy-intensive processes involved in their extraction and processing. This study focuses on sustainable alternatives by examining the use of steel slag, a by-product of the steel manufacturing industry, and locally available hard moorum (gravel) as partial replacements for conventional aggregates in pavement sub-base construction. The research includes a detailed analysis of the chemical composition and phase structure of slag using XRD techniques, as well as an evaluation of toxic and heavy metal content through leachate testing. Physical characteristics such as gradation, specific gravity, and impact resistance are assessed according to MoRTH guidelines. Experimental blending with crushed aggregates helped establish optimal usage rates of up to 80% slag and 50% moorum, both of which met the necessary gradation standards. To enhance the strength of moorum-based mixtures, cement stabilization was also introduced. Tests like Unconfined Compressive Strength (UCS) and California Bearing Ratio (CBR) demonstrated the mechanical viability of these materials in base and sub-base layers. The study concludes that both slag and moorum are not only technically suitable but also environmentally beneficial for use in road construction, offering a sustainable and cost-effective solution to the growing need for alternative construction materials.